Basquete, memória e "espírito mackenzista": um recorte a partir do acervo do Centro Histórico e Cultural Mackenzie (1896-2000) - Messias, David (2019)
This research analyzes the history of sport, especially basketball and its arrival in Brazil through Professor Augustus F. Shaw in the late 19th century, with the purpose of integrating the educational curriculum of the Presbyterian project, driven by the Christian reformed worldview. An interdisciplinary analysis has been made on how this sport created connections with educational, cultural and artistic matters, to the point of promoting what is known as the “mackenzist soul”, something that became part of the imaginary that forged Mackenzie in its emergence and becomes a fundamental part of the institution's existence in contemporary times. There are also glances on the aspects of the inclusion foreseen in the Presbyterian project that arrived with the missionaries from the USA who created Escola Americana, later Mackenzie College, and finally what is known today as Universidade Presbiteriana Mackenzie, so that through basketball, women and children were invited to take part in these practices. Concrete symbols and their aesthetic value are analyzed through the trophies and pennants that were conquered by the teams in competitions, becoming encouragement and link between generations to solidify the “mackenzist soul”. Finally, the impact of this “soul” over the creation of Mackenzie community is analyzed, as well as how it helped in the humanistic formation of thousands of people, working concepts such as otherness, union, fraternity, respect, etc., resulting in the perception and sense of peculiar belonging of Mackenzie’s students, teachers, supporters and service providers, who consider themselves “forever mackenzists”.